How ordinary consumers make complex economic decisions: Financial literacy and retirement readiness - Annamaria Lusardi; Olivia S. Mitchell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
This paper explores who is financially literate, whether people accurately perceive their own economic decision-making skills, and where these skills come from. Self-assessed and objective measures of financial literacy can be linked to consumers' efforts to plan for retirement in the American Life Panel, and causal relationships with retirement planning examined by exploiting information about respondent financial knowledge acquired in school. Results show that those with more advanced financial knowledge are those more likely to be retirement-ready.
urn:nbn:de:hebis:30-78630
Keywords: D91; 330; Financial Knowledge; Financial Sophistication; Retirement Planning; Alterssicherung; Finanzmarkt; Wissen; Lebensverlauf; Altersgrenze; USA